2021
DOI: 10.3389/fped.2021.661416
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Biotinidase Deficiency. The Experience of a Regional Center in Italy

Abstract: Introduction: Biotinidase deficiency (BD) is an autosomal recessive disease causing a defect in the biotin-releasing enzyme. Newborn screening (NBS) allows early diagnosis and treatment, ensuring excellent prognosis. The aim of this study was to describe our experience in the diagnosis, treatment, and follow-up showing key strategies and unsolved questions of the management of BD patients.Methods: We analyzed data of patients identified by the Regional Centre for Newborn Screening of Verona and followed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This mutation has a high prevalence among the European population and was also reported in other regions of the world. 63 These results indicate, that D444H is the common variant in BTD gene and that may be used as a biomarker for the purpose of prenatal diagnosis.…”
Section: Mutations In Other Populationsmentioning
confidence: 78%
“…This mutation has a high prevalence among the European population and was also reported in other regions of the world. 63 These results indicate, that D444H is the common variant in BTD gene and that may be used as a biomarker for the purpose of prenatal diagnosis.…”
Section: Mutations In Other Populationsmentioning
confidence: 78%
“…In Italy, the following incidences have been reported: combined profound BD between 1:61,000 and 1:6215 and partial BD between 1:137,236 and 1:7172 [12,26]. In a recent work, a higher incidence has been reported: 1:58,757 profound DB and 1:6677 partial BD [13].…”
Section: Discussionmentioning
confidence: 92%
“…Changes in the method for BTD activity assay from colorimetric to the more sensitive fluorometric can also lead to increased detection rate of the screening programs over time [9]. In the more recent studies, a higher incidence has been reported in some countries, such as Brazil, Turkey, and Italy [6,[10][11][12][13][14]. The clinical presentation of BD is variable mostly in relation to the degree of the residual enzyme activity, although different expressions in a family with the same genotype has been reported [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of mass spectrometry led to numerous pilot projects during the last two decades. Reports on regional NBS programs including those based on MS/MS have been published [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%